2006
DOI: 10.1152/ajpcell.00629.2005
|View full text |Cite
|
Sign up to set email alerts
|

TREK-2 (K2P10.1) and TRESK (K2P18.1) are major background K+ channels in dorsal root ganglion neurons

Abstract: Dorsal root ganglion (DRG) neurons express mRNAs for many two-pore domain K(+) (K(2P)) channels that behave as background K(+) channels. To identify functional background K(+) channels in DRG neurons, we examined the properties of single-channel openings from cell-attached and inside-out patches from the cell bodies of DRG neurons. We found seven types of K(+) channels, with single-channel conductance ranging from 14 to 120 pS in 150 mM KCl bath solution. Four of these K(+) channels showed biophysical and phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
221
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 187 publications
(244 citation statements)
references
References 34 publications
(49 reference statements)
17
221
1
Order By: Relevance
“…In an opposite manner, stimulation of the Gi-coupled adrenergic (α2AR), glutamate (mGluR2, mGluR4), γ-aminobutyrate (GABA B R) receptors activates TREK1 and TREK2 through adenylate cyclase inhibition, producing a decrease of cyclic adenosine monophosphate and PKA activity favoring channel dephosphorylation (3,8,38). Phosphorylation by PKC induces inhibition of TREK1 and/or TREK2 by Gq-coupled receptors through TSH releasing hormone receptor, orexin, acetylcholine (M3-R), and neurotensin (1,15,36). Other pathways contributing to Gq-mediated inhibition of TREK channels include mGluR1 activation through direct diacylglycerol and phosphatidic acid effects or through phosphatidylinositol 3,5-bisphosphate breakdown rather than activation of PKC (29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an opposite manner, stimulation of the Gi-coupled adrenergic (α2AR), glutamate (mGluR2, mGluR4), γ-aminobutyrate (GABA B R) receptors activates TREK1 and TREK2 through adenylate cyclase inhibition, producing a decrease of cyclic adenosine monophosphate and PKA activity favoring channel dephosphorylation (3,8,38). Phosphorylation by PKC induces inhibition of TREK1 and/or TREK2 by Gq-coupled receptors through TSH releasing hormone receptor, orexin, acetylcholine (M3-R), and neurotensin (1,15,36). Other pathways contributing to Gq-mediated inhibition of TREK channels include mGluR1 activation through direct diacylglycerol and phosphatidic acid effects or through phosphatidylinositol 3,5-bisphosphate breakdown rather than activation of PKC (29).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, inhibition of TREK1 by spadin (10), an endogenous peptide, or by the antidepressant fluoxetine (Prozac) (11), pinpoints it as a valuable target for the treatment of depression. TREK/TRAAK channels are broadly expressed in the nervous system (12)(13)(14)(15). TREK1 is more specifically expressed in the striatum, TREK2 in the cerebellum, and TRAAK in the thalamus.…”
mentioning
confidence: 99%
“…Thus, we conclude that KCNK channels are the likely targets of sanshool action. Indeed, members of this two-pore K + channel subfamily (KCNK2, KCNK3, KCNK9, KCNK10 and KCNK18) have been proposed to set the resting membrane potential of primary afferent sensory neurons, with KCNK18 (TRESK) having the predominant role [19][20][21] .…”
Section: Sanshool Inhibits a Ph-sensitive K + Leak Conductancementioning
confidence: 99%
“…In contrast, KCNK18 transcript levels were significantly more abundant (13.1 ± 1.2-fold) in trigeminal ganglia than in CGNs at day 2 or 7, suggesting that this subtype has an important role in mediating sanshool sensitivity of primary sensory neurons. Indeed, among sanshool-sensitive KCNK subtypes, KCNK18 contributes significantly to the background K + current in cultured DRG neurons 20 . Moreover, in situ hybridization histochemistry suggests that KCNK18 transcripts are expressed by a significant fraction of primary sensory neurons 21 .…”
Section: Sanshool Sensitivity Correlates With Kcnk Subtype Expressionmentioning
confidence: 99%
“…In general, these channels are closed at low temperatures (< 30 °C) but are activated by polyunsaturated fatty acid, increasing cellular volume, protons and general anesthetics [5,7]. It has been demonstrated that the mRNAs and proteins of 5 these channels are widely expressed in both the central and peripheral nervous systems using reverse transcriptase-polymerase chain reaction (RT-PCR; [10]), in situ hybridization [13] and immunohistochemistry [4].…”
mentioning
confidence: 99%